Chromatin Modifications as Determinants of Muscle Stem Cell Quiescence and Chronological Aging - Liu, Ling; Cheung, Tom H.; Charville, Gregory W.; Hurgo, Bernadette Marie Ceniza; Leavitt, Tripp; Shih, Johnathan; Brunet, Anne; Rando, Thomas A. (Cell reports (Cambridge), 2013)
The ability to maintain quiescence is critical for the long-term maintenance of a functional stem cell pool. To date, the epigenetic and transcriptional characteristics of quiescent stem cells and how they change with age remain largely unknown. In this study, we explore the chromatin features of adult skeletal muscle stem cells, or satellite cells (SCs), which reside predominantly in a quiescent state in fully developed limb muscles of both young and aged mice. Using a ChIP-seq approach to obtain global epigenetic profiles of quiescent SCs (QSCs), we show that QSCs possess a permissive chromatin state in which few genes are epigenetically repressed by Polycomb group (PcG)-mediated histone 3 lysine 27 trimethylation (H3K27me3), and a large number of genes encoding regulators that specify nonmyogenic lineages are demarcated by bivalent domains at their transcription start sites (TSSs). By comparing epigenetic profiles of QSCs from young and old mice, we also provide direct evidence that, with age, epigenetic changes accumulate and may lead to a functional decline in quiescent stem cells. These findings highlight the importance of chromatin mapping in understanding unique features of stem cell identity and stem cell aging. [Display omitted] •Chromatin modification pattern on myogenic regulatory factor genes in QSCs•Chromatin modification pattern on myogenic regulatory factor genes in QSCs•Increase in H3K27me3 across the genome in adult QSCs with age•Decrease of histone expression in adult QSCs with age The comprehensive transcriptional and chromatin modification profile of an adult quiescent stem cell population, skeletal muscle satellite cells, is now examined by Rando and colleagues. The authors characterize changes associated with satellite cell activation and aging, providing direct evidence for global changes in histone modifications in adult stem cells with age.